CHOICE OF THE METHOD OF SURGICAL TREATMENT OF CHRONIC PANCREATITIS - A. V. Vorobei; A. Ch. Shuleiko; Yu. N. Orlovskiy; Yu. I. Vizhinis; Yu. V. Butra; N. A. Lagodich (Вестник хирургии имени И.И. Грекова)
An analysis of surgical treatment of 187 patients with chronic pancreatitis was made during 3-year period in the department of surgery clinic of Byelorussian Medical Academy of Post-Graduate Education. Drainage operations were performed on 28 patients, resection-drainage operations were carried out on 130 patients and resection operations had 19 patients. The laser beam technologies were successfully applied during operations on the pancreas in 43 patients. Postoperative complications (14,8%) were analyzed and structured. Methods of corrections and ways of prophylaxis of complication development were provided. On the basis of the complication analysis and new conception concerning peripheral pancreatic hypertension the authors offered the rational approaches to choice of operations on the pancreas in case of chronic pancreatitis. The authors developed the classification of pancreatoductolitiasis, pancreatic hypertension and a new strategy of surgical management of chronic pancreatitis.